Outage Performance of Flexible OFDM Schemes in Packet-Switched Transmissions. (29th August 2009) - Couillet, Romain; Debbah, Mérouane
Abstract : α -OFDM, a generalization of the OFDM modulation, is proposed. This new modulation enhances the outage capacity performance of bursty communications. Theα -OFDM scheme is easily implementable as it only requires an additional time symbol rotation after the IDFT stage and a subsequent phase rotation of the cyclic prefix. The physical effect of the induced rotation is to slide the DFT window over the frequency spectrum. When successively used with different anglesα at the symbol rate, α -OFDM provides frequency diversity in block fading channels. Interestingly, simulation results show a substantial gain in terms of outage capacity and outage BER in comparison with classical OFDM modulation schemes. The framework is extended to multiantenna and multicellular OFDM-based standards. Practical simulations, in the context of 3GPP-LTE, called hereafterα -LTE, sustain our theoretical claims.